Is deflation costly after all? Evidence from noisy historical data - Daniel Kaufmann (ETH Zurich, KOF Swiss Economic Institute, 2016)
I study the link between real activity and deflation, taking into account measurement problems in 19th century CPI data. Replications based on modern data show that measurement problems spuriously increase the volatility of inflation as well as the number of deflationary episodes, and they lower inflation persistence. As a consequence, estimates of the link between real activity and deflation may be attenuated because of the errors-in-variables problem. I find that real activity was on average substantially lower during 19th century deflations in the US, after controlling for measurement error using an IV-regression approach. Moreover, the average short-fall in real activity was not significantly different compared to the Great Depression. Using well-measured data for a panel of 17 industrialized economies shows that milder deflations were associated with a lower output gap. But, the association with GDP growth is not statistically significant.
Keywords: E31; E32; N11; C36; 330; Deflation; real activity; measurement error; monetary history; IV